39.1k views
0 votes
Find the product........................................

Find the product........................................-example-1
User Eric Klaus
by
6.1k points

1 Answer

4 votes

For this case we must find the product of
(2x + 3) (2x-3), for this, we must apply the distributive property, which by definition establishes that:


(a + b) (c + d) = ac + ad + bc + bd

So:


(2x + 3) (2x-3) = (2x) ^ 2 + (2x) (- 3) + (3) (2x) + (3) (- 3)

considering that
+ * - = -


(2x + 3) (2x-3) = 4x ^ 2-6x + 6x-9\\(2x + 3) (2x-3) = 4x ^ 2-9

Answer:

Option A


User Joe Lewis
by
5.7k points